Featured Cover. (15th December 2021) - Ahmmed, Fatema; Fraser‐Miller, Sara J.; Garagoda Arachchige, Piumika Samanali; Schallenberg, Marc; Novis, Phil; Gordon, Keith C.
Abstract : The cover image is based on the Special Issue – Research Article Lake snow caused by the invasive diatom Lindavia intermedia can be discriminated from different sites and from other algae using vibrational spectroscopy by Fatema Ahmmed et al., https://doi.org/10.1002/jrs.6161 .